2006
DOI: 10.1016/j.diamond.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Different morphologies of carbon nanotubes effect on the lead removal from aqueous solution

Abstract: Four kinds of CNTs with different morphologies were produced by chemical vapour deposition method. After oxidation with nitric acid, their specific surface area, particle size distribution and functional groups on the surfaces were characterized. Adsorption isothermal experiment shows that the CNTs with more defects, which can be easily introduced more functional groups on their surfaces prepared at 650 -C, have higher lead adsorption capability from aqueous solution and are promising adsorbents in wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…In addition, with a small (B10 nm) UCNT diameter, their modified outer layers are easily accessible to the solution. Consequently, a high salt adsorption capability was achieved with the modified UCNTs when salt water flowed through the porous structure 35,36 . It is worth mentioning that samples ii-iv could completely remove salt below the detection threshold of 10 -7 M from the solution in the first round of the filtration process (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, with a small (B10 nm) UCNT diameter, their modified outer layers are easily accessible to the solution. Consequently, a high salt adsorption capability was achieved with the modified UCNTs when salt water flowed through the porous structure 35,36 . It is worth mentioning that samples ii-iv could completely remove salt below the detection threshold of 10 -7 M from the solution in the first round of the filtration process (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A lead sorption study with CNTs was carried out by Li et al [20] at pH 7 and equilibrium concentration range of 10-80 μeq/L where the sorption capacity was reported as 482 μeq/g. In another study, Li et al [24] reported that the lead sorption capacity of CNTs at pH 5 was 797 μeq/g. The lead sorption capacity on NPC is significantly higher (2000 μeq/g) than on these CNTs.…”
Section: Isotherm Studiesmentioning
confidence: 99%
“…CNTs were found to be superior sorbents for inorganic pollutants such as fluoride [18], and several divalent metal ions [7,8,[19][20][21][22][23][24][25]. Li et al [24] reported that CNTs with more defects and poor quality possess higher surface area and exhibit better lead sorption capacity compared to aligned CNTs. Activation of CNTs plays an important role in enhancing the maximum sorption capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations